Environmental and economic assessment of hydrogen compression with the metal hydride technology. (26th February 2022) - Costamagna, Mattia; Barale, Jussara; Carbone, Claudio; Luetto, Carlo; Agostini, Alessandro; Baricco, Marcello; Rizzi, Paola
Abstract: A critical step in the hydrogen supply chains is the compression phase, which is often associated with high energy consumption and environmental impacts. An environmental and cost analysis of a metal hydride (MH) compressor and competing technologies (an air booster and a commercial hydrogen compressor), is performed for an application to fuel cell driven forklifts. The MH compressor shows limited environmental impacts only when a source of waste heat is available for hydrogen desorption. In these case, impacts would be similar to a generic compressor, but larger than those generated by an air booster. The equivalent economic cost is 6 € per kg of compressed hydrogen for the MH compressor, which is much higher than for the air booster, but lower than for a generic hydrogen compressor. Technical aspects to be improved for large-scale applications of MH compressors are identified. Highlights: Environmental and costs analysis of a metal hydride compressor have been established. Environmental and costs comparison of different H2 compression solution. Metal hydride compressors show limited impact only under specific working conditions. The alloys, used for the hydrogen sorption, show limited environmental impacts.